Solar Water Splitting: Hollow Multishelled Structured SrTiO3 with La/Rh Co‐Doping for Enhanced Photocatalytic Water Splitting under Visible Light (Small 22/2021). Issue 22 (2nd June 2021) - Wei, Yanze; Wan, Jiawei; Wang, Jiangyan; Zhang, Xing; Yu, Ranbo; Yang, Nailiang; Wang, Dan
Abstract : In article number 2005345, Ranbo Yu, Dan Wang, and co‐workers successfully incorporate the advanced structural design to construct the La‐ and Rh‐ co‐doped SrTiO3 (STO:La/Rh) hollow multi‐shelled structures (HoMSs). The elevated visible light responsive photocatalytic water splitting performances give a promising prospect for HoMSs‐based materials in photocatalytic and photo related fields. With a broad vision, the authors foresee that the dawn of HoMSs photocatalyst is arriving with more innovative evolutions.